Depletion of Indonesian oil palm plantations implied from modeling oil palm mortality and Ganoderma boninense rot under future climate - Paterson, R. R. M. (2020)
Currently there are increasing land-cover change and land-management issues related to oil palm plantations. Palm oil is highly valuable and it is added to numerous commodities internationally with Indonesia being the most voluminous producer. The cultivation of oil palm affects the environment negatively, per se, threatening plantation sustainability from deforestation. Furthermore, the fungus Ganoderma boninense causes basal stem rot of oil palm, a major problem for plantation managers in Indonesia. Suitable future climate for growth of Indonesian oil palm, determined by employing the simulation programme, CLIMEX, has already been employed to create scenarios of oil palm mortality and diseases. This was achieved by combining CLIMEX with narrative models, a technique often employed in climate studies. Determinations of the percentage of oil palm that survive climate change and do not have basal stem rot have also been provided. The current paper considers these scenarios for Indonesia and regions for the first time. The models assume no change in the future climate scenarios and that effective mitigation is not taken. The effects on plantation sustainability are considered. Climate change will not affect the incidence of basal stem rot greatly until 2050, but the situation will deteriorate thereafter. Sumatra and Java are especially affected and plantations may be unsustainable quickly, whereas Papua and Sulawesi may be able to sustain the crop longer. However, deforestation in Papua and Sulawesi is highly undesirable. Methods to manage climate change effects on oil palm and reduce basal stem rot are described. Plantation managers can use the earlier assessments herein to indicate if the later ones are accurate and plan to ameliorate the problems. Conclusions indicate that palm oil production may be unsustainable in Indonesia by 2050 from loss of plantations thus requiring action immediately.